Sex-specific gene expression and weighted co-expression network analysis suggest distinct sex-specific molecular signatures in acutely suicidal MDD-patients without somatic comorbidities - Fritz, Michael; Holzmann, Karlheinz; Castany, Silvia; Haas, Heidrun; Montag, Christian; Engblom, David; Streb, Judith; Dudeck, Manuela (Frontiers in Genetics, 2025)
IntroductionMajor depressive disorder (MDD) is a debilitating psychiatric disorder and is strongly associated with suicidal ideation and acute suicidality. While sex differences are evident across nearly all stages of depression, sex-specific mechanisms in acute suicidality remain not fully understood. This gap is notable given that women are twice as likely as men to develop depression, show earlier onset and greater symptom severity, and account for two-thirds of suicide attempts, whereas men have higher suicide completion rates. At the molecular level, sex differences also influence pharmacological treatment response, yet the biological mechanisms underlying these disparities remain not fully understood.MethodsIn an exploratory approach, we investigated genome-wide gene expression changes in peripheral blood from 14 acutely suicidal patients with MDD (seven females, seven males) without comorbid somatic conditions, compared with sex-matched healthy controls. Gene expression profiles, generated using Affymetrix microarrays, were corrected for multiple testing and further examined through Gene Ontology enrichment, Gene Set Enrichment, Weighted Gene Co-expression Network, and Protein–Protein Interaction analyses.Results/DiscussionWhen analyzed as a combined group, suicidal MDD patients exhibited 87 differentially expressed genes (DEGs). However, stratification by sex revealed 665 DEGs in females, whereas no significant DEGs were detected in males. These findings, validated through pathway- and network-level analyses, suggest that previous studies pooling male and female MDD patients may have overlooked sex-specific effects. Nevertheless, given the small group number of patients, it cannot be excluded that the absence of DEGs in males may be due to a coincidental genetic profile of the group. Larger confirmatory studies, or re-analyses of existing datasets with sex-specific stratification, are therefore essential. In female suicidal MDD patients, both single-gene and pathway-oriented analyses highlighted immune and inflammatory processes, particularly the NF-κB pathway, consistent with prior evidence and pointing to additional targets such as tumor necrosis factor–alpha inducible protein 6.ConclusionCollectively, these findings underscore the critical importance of sex-specific molecular research in acutely suicidal MDD patients and may inform the development of more targeted therapeutic approaches.